Austerity policies: towards local environmental empowerment or neoliberal conservation? - Maforimbo, C (2018)
The United Kingdom’s government has been sharply reducing its size by exercising austerity on its departments since 2010, with the narrative that this will create opportunity for more localized scales to deliver services and be more empowered. Drawing on the Politics of Scale and Networks with an emphasis on conservation, this research uses semi-structured interviews with principal local authority conservation officers and local conservation charities to map the geographies of power that have resulted from central government’s measures, thus testing to what extent their localism narrative has come to pass. We find that some power was indeed transferred to the local scale, but only partially, specifically to established charities, while emerging charities were weakened. We also find evidence that suggests neoliberal motives for effecting the austerity. This research contributes to the scarce literature that delves into the effect of austerity on conservation capacity at localised scales and the debate against austerity.